The Wolf and the Crane and other stories (big book) - Akhtar, Nasreen (Children Publication Karachi, 2020)
"The Wolf and the Crane and Other Stories" is a collection of fables that features various animals and imparts important life lessons. In the titular tale, a wolf injures his mouth while eating a bone and asks a crane to help remove it, promising a reward. After the crane successfully helps him, the wolf instead reveals his true nature and offers nothing in return, teaching a lesson about ingratitude and the dangers of trusting those who are deceitful. Other stories in the collection explore themes such as cleverness, honesty, and the consequences of one's actions, all presented through engaging narratives and memorable characters. Each tale concludes with a moral, making the collection both entertaining and educational for young readers.